ANALISIS KINERJA PEGAWAI DINAS PENDIDIKAN PROVINSI JAWA TENGAH (STUDI PENGAMATAN PADA SUB BAGIAN UMUM DAN KEPEGAWAIAN) - Hasbi Hafis; Mochammad Mustam; Rihandoyo Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The purpose of this research is to know the correlation between employee ability, employee motivation, leadership, organizational climate, work relationship and initiative with employee performance in Education Office of Central Java Province (Observation Study at Sub Division General and Personnel). The population of 64 employees with samples taken as many as 39 employees. Hypothesis test using correlation pearson product moment to find out the correlation between each independent variable with dependent variable, and coefficient of determination analysis to measure how far the model ability in explain variation of independent variable. The findings of the results show that the hypothesis that there is a positive correlation between the ability of employees, employee motivation, leadership, organizational climate, employment relations and initiatives with the performance of employees of the Central Java Provincial Education Office (Observation Studies on Sub Division General and Personnel), can be received significantly the correlation coefficient value of each relationship is the correlation between the ability of employees with employee performance is 0.415, the correlation between employee motivation and employee performance is 0.313, the correlation between leadership with employee performance is 0.581, the correlation between organizational climate with employee performance is 0.577, correlation between employment relationship with employee performance is 0.210 and the correlation between initiative with employee performance is 0.561. For the coefficient of determination (R2) is shown in Kendall's W coefficient of 0.579.